Electrically tunable Fabry-Pérot resonator based on microstrcutured Si containing liquid crystal - PEROVA, TANIA (My University, 2012)
We have built Fabry-Perot resonators based on mi-crostructured silicon and a liquid crystal. The devices exhibit tuning of the resonance peaks over a wide range, with relative spectral shifts of up to ??/? = 10%. In order to achieve this substantial spectral shift, cavity peaks of high order were used. Under applied voltages of up to 15 V, a variation in the refractive index of the nematic liquid crystal E7 from ?nLC = 0.12 to ?nLC = 0.17 was observed. These results may have practical applications in the near-, mid and far-infrared range.
PUBLISHED
Keywords: Optics; Silicon photonics; Nanoscience & Materials